(untitled) (Journal of Philosophy Culture and Political Science, 2015)
The article analyzesthe activities and outlook of Khwaja AhmadYasawi as the founder of Sufism, the Turkic branch of Islam. There are numerous written records about the identity, activity of Khwaja Ahmad Yasawi, which characterize him as one of he pillars of Turkic culture. The conclusion about the nature of his religious and philosophical worldview based on the analysis of his work «Diwani-i-Khikmet». Based on the pantheistic idea of the dissolution of God in nature, man comes to thinking about the possibility of moral perfection through the knowledge of God. This paper examines this work as the founder of Sufism, which has such important aspects as: the adaptation of Islam to the Turkic environment, the Association of Turkic peoples into a single cultural and political community, the creation of the order of Yasawi, raising the status of Turkic language, acquaintance through khikmets with Eastern philosophy and poetry.